Micronutrients release from active polyethylene films under mulched conditions - Paula B. Linares; Luciana A. Castillo; Silvia E. Barbosa (Results in Surfaces and Interfaces)
The aim of this work is to analyze the release of micronutrients from surface modified polyethylene films for active mulch application under field-like conditions. In this way, surface modified polyethylene films with mineral particles (talc, zeolite and calcium carbonate) and sprayed with saturated salt solutions (iron sulfate, copper sulfate and manganese sulfate) as micronutrient sources were analyzed. The resulting active films were subjected to a specific release experiment to simulate conditions similar to those of mulch in the field. In this sense, these films were placed inside a closed system and then they were exposed to continuous cycles of water evaporation/condensation. The amount of released micronutrients in collected liquid was measured by Atomic Absorption at different times. Meanwhile, the presence of micronutrients on films surface, before and after the release experiment, was analyzed by Scanning Electron Microscopy/Energy Dispersive X-ray Spectrometry. Micronutrients were successfully released from active films under continuous cycles of water evaporation/condensation, reaching a maximum for all active films before 50 days. Talc modified films resulted more efficient for releasing Fe and Cu, meanwhile films modified with calcium carbonate released a greater amount of Mn under similar conditions. After the release experiment, all active films retained iron sulfate, copper sulfate and, to a lesser extent, manganese sulfate, suggesting the potential of prolonged release. These active films are promissory for mulch applications since it was demonstrated that released micronutrients provide a sustained supply to satisfy the nutritional requirements of crops, mainly in depleted soils.